TRANSFORMATION OF EDUCATION INTO DIGITAL WORLD (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2024)
In the 21st century, it is already impossible to imagine the educational process without the use of information technologies, which allow teachers to qualitatively change the content, methods and organizational forms of training. The development of electronic teaching aids makes it possible to dynamically change and supplement the content of training in accordance with current changes in society, science, culture, etc